ChemInform Abstract: Unexpected Copper‐Catalyzed Cascade Synthesis of Quinazoline Derivatives. Issue 14 (8th April 2014) - Chen, Zhongyan; Chen, Jiuxi; Liu, Miaochang; Ding, Jinchang; Gao, Wenxia; Huang, Xiaobo; Wu, Huayue
Abstract The title reaction represents a new strategy for the construction of 2‐substituted quinazolines.